PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PT SUMBER AGRINDO SEJAHTERA PONTIANAK - Hendra, Hendra Aprianto B1021141077 (Jurnal Manajemen Update, 2019)
ABSTRAK Employee performance is the most important element in achieving satisfying company performance. Performance and productivity will be achieved if employees working in the organization feel satisfaction in working. Leadership is an important factor in determining the behavior of individuals and groups in organizations because leadership can foster morale and job satisfaction of its members which results in increased performance. One way managers can improve job satisfaction and employee performance is through compensation.PT Sumber Agrindo Sejahtera Pontianak is a company engaged in oil palm plantations that are experiencing the impact of the financial crisis so that there is employee dissatisfaction and the impact of a very significant decrease in employee performance. This study aims to examine the factors of leadership and compensation for job satisfaction and employee performance. The type of research used in this study is causality research with Path Analysis data analysis techniques. Data was obtained from 54 respondents who were employees of PT Sumber Agrindo Sejahtera Pontianak by distributing closed questionnaires.The results of this study indicate that leadership variables (X1) have no significant effect on job satisfaction (Y1), compensation has a significant effect on job satisfaction (Y1), leadership has no significant effect on performance (Y2), compensation has a significant effect on performance (Y2) and Job satisfaction (Y1) has a significant effect on performance (Y2). Keyword: Leadership, Compensation, Job Satisfaction, PerformanceDAFTAR PUSTAKA Ardana, I. K., Mujianti, N. W., & Utama, I. W. M. (2012). Manajemen Sumber Daya Manusia. Yogyakarta: Graha Ilmu. Bangun, W. (2012). Manajemen Sumber Daya Manusia. Jakarta: Erlangga. Fithriana, N., & Adi, A. N. (2017, Desember). Dominant Effect Between Compensation, Leadership and Organization Culture On Employee Performance Improvement. Journal of Applied Management, 15 (04), 670-676.Hasibuan, H. M. (2006). Manajemen Dasar, Pengertian, dan. Masalah, Edisi Revisi, Jakarta: Bumi Aksara. Lazuardy, T., Away, Y., & Majid, M.S.A. (2014). Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Pegawai Negeri Sipil Setda Kab Aceh Barat Daya. Jurnal Manajemen Pascasarjana Universitas Syiah Kuala. 3 (02), 94-101.Lukas, M., Tewal, B., & Walangitan, M. D. (2017, Juny). Pengaruh Pengawasan, Kepemimpinan dan Kompensasi Terhadap Kinerja Pegawai Pada Badan Pengelola Keuangan dan Barang Milik Daerah Kabupaten Minahasa Utara. Jurnal Emba, 05 (02), 1921-1928.Mangkunegara. A.A.P. (2013). Manajemen Sumber Daya Manusia Perusahaan. Bandung: Remaja Rosdakarya.Nizamuddin., Sagal, S., & Napitupulu, E. (2018, January). Effect of Leadership, Organizational Structure, Compensation, and Motivation Toward Performance of Aggregat Data Control on The Statistics Center North Sumatera Province. International Journal of Education and Research, 06 (01), 167-180.Pioh, N.L., & Tawas, H.N. (2016). Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja dan Kinerja Pgawai (Studi Pada PNS di Kantor Kecamatan Sonder Kabupaten Minahasa). Jurnal EMBA. 4 (02), 838-848.Rivai, V., Ramly, M., Mutis, T., & Arafah, W. (2014). Manajemen Sumber Daya Untuk Perusahaan: Dari Teori ke Praktik. Jakarta: Raja Grafindo Persada. Siagaan, P. S. (2003). Produktivitas Kerja Perusahaan. Jakarta: Raja Grafindo Persada. Suparyadi. (2015). Manajemen Sumber Daya Manusia. Yogyakarta: Andi Offset. Suprapta, M., Sintaasih, D.K., & Riana, I.G. (2015). Pengaruh Kepemimpinan Terhadap Kepuasan Kerja dan Kinerja Karyawan (Studi Pada Wake Bali ASrt Market Kuta-Bali). E-Jurnal Ekonomi dan Bisnis Universitas Udayana. 04 (06), 430-442. Wirawan. (2015). Manajemen Sumber Daya Manusia Indonesia: Teori, Psikologi, Hukum Ketenagakerjaan, Aplikasi dan Penelitian: Aplikasi dalam Organisasi Bisnis, Pemerintahan dan Pendidikan. Jakarta: RajaGrafindo Persada.